Physico-Chemical Studies on Bore Wells Water of Dahod [Gujarat] - Rana, A.K.; Kharodawala, M.J.; Dabhi, H.R.; Suthar, D.M.; Dave, D.N.; Patel, B.S.; Rai, R.K. (Asian Journal of Chemistry, 2010)
Physico-chemical analysis such as temperature, pH, dissolved oxygen, total dissolved solids, chloride, total alkalinity, calcium and magnesium hardness, sulphate, phosphate and nitrate of borewells water was carried out from twenty sampling stations of Dahod city, Gujarat and its some interior adivasi area during the year 1999–2000.